Tracing the affordances of long-acting injectable depot buprenorphine: A qualitative study of patients' experiences in Australia. (1st October 2021) - Barnett, Anthony; Savic, Michael; Lintzeris, Nicholas; Bathish, Ramez; Arunogiri, Shalini; Dunlop, Adrian J.; Haber, Paul; Graham, Robert; Hayes, Vicky; Lubman, Dan I.
Highlights: Interviews (n = 30) explored Australian patients' experiences of depot buprenorphine. Often, depot buprenorphine afforded more time to engage in travel, work and study. For a few participants, depot buprenorphine disrupted important clinical supports. Depot buprenorphine is experienced in varying ways for different patients. Clinical teams should closely monitor new patients receiving depot buprenorphine. Abstract: Background: Long-acting injectable depot buprenorphine is an important new treatment option for the management of opioid dependence, delivering therapeutic doses in weekly or monthly formulations. Depot buprenorphine aims to overcome challenges associated with traditional opioid agonist therapy (OAT), including: poor patient adherence; inconvenience of regular attendance for dosing; and, risk of non-medical use of takeaway doses. However, little is known about patients' experiences of depot buprenorphine. This qualitative study aimed to explore patients' experiences of the practical and social affordances of depot buprenorphine. Methods: Participants were recruited from sites in Sydney, regional New South Wales, and Melbourne, Victoria, Australia. Thirty participants (16 men, 14 women; mean age 47.3 years) participated in semi-structured interviews. Participants had histories of both heroin and prescription opioid use, and previous OAT including daily dosing of buprenorphine and methadone. Findings: Depot buprenorphine afforded positive benefits for many participants, including: opportunities to avoid stigma experienced at pharmacies/clinics; time to engage in activities (e.g., travel, work) by releasing participants from previous OAT treatment regimens; and, cost savings by not having to pay pharmacy fees associated with daily dosing. However, for some participants, moving to depot buprenorphine: disrupted engagements with important social/practical supports available at pharmacies/clinics; constrained their control over dosing; and, constrained their ability to generate income via the sale of takeaway doses. Conclusions: While generally experienced as affording benefits, depot buprenorphine can have differing social and practical impacts. Clinicians should monitor patients receiving depot buprenorphine to reduce the risk of unintended consequences including disruption to clinical supports.